Long-term physico-chemical and faunal changes in a small, rural South African estuary. Issue 4 (2nd October 2018) - Kajee, M; Griffiths, CL; Lamberth, SJ
Abstract : The Palmiet Estuary is a small, rural estuary in the Western Cape that only closes briefly during dry summers. The system was previously surveyed during 1979 to 1980 and we repeated the survey in April 2015 (mouth closed) and September 2015 (mouth open). Salinity, temperature, pH and oxygen saturation were measured, and invertebrate and fish faunas surveyed. Physico-chemical characteristics have undergone little directional change, apart from an apparent increase in pH, possibly as a result of changes in land use and application of fertilisers and pesticides in the catchment. Invertebrate species richness increased from 31 to 40 species, despite lower sampling effort in 2015. Most changes were among rare species, or were readily explained by changes in mouth condition and water chemistry. We also confirmed a substantial range extension of the tropical crab, Varuna litterata, rediscovered the locally endemic amphipod, Quadrivisio aviceps, and reported several new distribution records. Gastropods had virtually disappeared from the system, whereas the previously unreported bivalve, Brachidontes virgilae, had become abundant. Overall, fish diversity dropped from 19 to 11 species, but this can largely be ascribed to differ- ences in sampling frequency, season and mouth state. Comparisons of samples from like months showed the fish assemblage to have remained fairly stable, despite changes in inflowing water chemistry and infection of fish by the pathogenic water mould, Aphanomyces invadans. Bird abundance and diversity increased substantially. No alien invertebrate or fish species were recorded. Accordingly, in marked contrast to other smaller estuaries in the region, the Palmiet Estuary has remains in relatively good condition.